Karakterisasi dan Seleksi Beberapa Isolat Azotobacter sp. untuk Meningkatkan Perkecambahan Benih dan Pertumbuhan Tanaman - H Widiastuti; nFN Siswanto; nFN Suharyanto (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2010)
Characterization and Selection of Azotobacter sp. in Enhancing Seed Germination and Growth of Plant. Nitrogen (N) is a macro nutrient needed by the plant. Chemical synthesis of N fertilizer need high energy input. On the other hand, Azotobacter sp. has been known as a free living nitrogen fixing bacteria. This bacteria is also known as growth factor producing bacteria such as indole acetic acid (IAA) and extracellular polysaccharide. The ability of Azotobacter sp. in fixing N and producing IAA was affected by strain type of the bacteria as well as the origin of the isolate. It had been characterized 44 isolates of Azotobacter sp. isolated from selected dry habitat such as oil palm in Sekayu (South Sumatera), coffee and cashew nut tree in NTT, corn crops in Banjar (South of Kalimantan), and rubber tree in Bogor (West Java). Isolation was conducted using Ashby media. Based on their ability in producing IAA, promoting germination of the seed and growth of leguminous cover crops Pueraria phaseoloides. The result showed that isolate of 116(2), from Sikka, Flores, (NTT), produced highest IAA i.e 2.815 μM within the third day and 4.02 uM in the sixth day incubation time. Strain D1/8B (isolated from oil palm plantation in South Sumatera) and S5 (isolated from corn in South Kalimantan) could increase 2-3 times number of germinating seed of P. phaseoloides for the third days. Azotobacter sp. isolate of D1/2, 107, and 113 in combination with 50% recomended doses of chemical fertilizer could enhance the growth of plant (fresh and dry biomassa total) of sorghum higher compared to 100% chemical fertilizer doses (control). Isolate of D1/2 originated from South of Sumatera improved germination of seed, and enhanced the growth of sorghum, while isolate of 113 from Sikka, Flores, NTT had the ability to increase the growth of sorghum during one month in glass house experiment. AbstrakNitrogen (N) merupakan unsur makro yang diperlukan oleh tanaman. Bakteri Azotobacter sp. diketahui dapat memfiksasi N secara nonsimbiotik dan menghasilkan hormon tumbuh seperti IAA dan polisakarida ekstraseluler. Kemampuan penambatan N dan produksi IAA dipengaruhi oleh galur bakteri dan asal isolat. Penelitian dilakukan untuk mengkarakterisasi 44 isolat Azotobacter sp. yang diisolasi dari beberapa habitat lahan kering, yaitu perkebunan kelapa sawit di Sekayu (Sumsel), perkebunan kopi dan jambu mete di Nusa Tenggara Timur, areal tanaman jagung di Banjar (Kalsel), dan kebun karet di Bogor (Jabar). Isolasi bakteri Azotobacter sp. dilakukan menggunakan medium Ashby. Isolat yang diperoleh diuji kemampuannya menghasilkan IAA dan pengaruhnya terhadap perkecambahan benih serta pertumbuhan kacang penutup tanah (Pueraria phaseoloides). Hasil percobaan menunjukkan bahwa isolat 116 (2) menghasilkan IAA tertinggi, yaitu 2,815 μM pada hari ke-3 dan 4,02 μM pada hari ke-6. Isolat tersebut berasal dari Sikka, Flores, NTT. Isolat D1/8B (asal perkebunan kelapa sawit di Sumsel) dan S5 (asal areal tanaman jagung di Kalimantan) dapat meningkatkan 2-3 kali jumlah benih P. phaseoloides yang berkecambah pada hari ke-3. Isolat D1/2, 107, dan 113 dapat meningkatkan pertumbuhan tanaman sorgum (total biomasa basah dan kering) lebih tinggi dibandingkan dengan pupuk NPK 100%. Isolat D1/2 asal Sumsel meningkatkan perkecambahan benih dan pertumbuhan sorgum relatif tinggi, sedang isolat 113 asal Sikka, Flores, NTT, mampu meningkatkan pertumbuhan tanaman sorgum.